The workforce culture in a state university in the Philippines: Drivers of engagement - Docallas, Julie Grace M.; Codod, Christie Lynne C.; Cruz, Flordeliza (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to identify the primary drivers of employee engagement at a State University in the Philippines, focusing on exploring similarities and differences across faculty and staff groups. A quantitative survey was distributed to 232 faculty and staff respondents to collect data on factors influencing their engagement levels. Results revealed distinct engagement drivers for each employee group: Permanent Faculty prioritized employee trust, organizational integrity, inspirational leadership, and career growth opportunities. In contrast, Permanent Staff emphasized recognition through rewards for high performance and managerial support, highlighting the importance of acknowledgment and listening. These findings underscore the need for tailored human resource strategies that address unique engagement factors for each employee group within the university. The study recommends expanding leadership development programs, implementing comprehensive recognition and reward systems, and ensuring ample career advancement opportunities to foster a more engaged workforce. This research offers valuable guidance for improving organizational practices and fostering a more engaged workforce at the university.